Trade, Regulations, and Growth - Bolaky, Bineswaree (World Bank, Washington, DC, 2013)
Trade does not stimulate growth in economies with excessive business and labor regulations. The authors examine the effect of openness on growth using cross-country regressions in both levels and changes. Results from the levels regressions imply that increased openness is associated with a lower standard of living in heavily-regulated economies. Growth regressions confirm that the effect of increased trade on growth is absent in these countries. The authors also find that once they control for the effect of trade on growth in heavily regulated economies, the evidence that trade positively affects growth is stronger than has been found in previous studies. Excessive regulations restrict growth because resources are prevented from moving into the most productive sectors and to the most efficient firms following liberalization. In addition, in highly regulated economies, increased trade is more likely to occur in the wrong goods-that is, goods where comparative advantage does not lie. The results imply that countries must create a sound business environment before trade can be used as an engine of growth.